2019
DOI: 10.3897/subtbiol.32.36222
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of morphology and web geometry between hypogean and epigean species of Metellina orb spiders (family Tetragnathidae)

Abstract: Studies on the behaviour of subterranean animals are rare, mainly due to the problems with collecting data in these inaccessible habitats. Web-building cave spiders, however, leave a semi-permanent record of their foraging behaviour, which can relatively easily be recorded. In this study, we compare size, leg lengths and web characteristics between hypogean populations of Metellina merianae with its close wood-inhabiting relative M. mengei. We confirm previous observations that M. merianae does not show any ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…However, the number of capture spiral turns (17.0 ± 4.3) was considerably greater than recorded for M. menardi in this study (6.0 ± 1.7), suggesting that the mesh height would be lower. A similar number of radii (16.9 ± 3.0) and spiral turns (13.0 ± 3.0) were observed in the facultative cave spider M. merianae , but this species does not show any reduction of frame threads and only a few mooring threads connect the web to the cave wall 41 . Interestingly, the webs of M. menardi were more symmetrical than the webs of the two surface-dwelling species.…”
Section: Discussionsupporting
confidence: 54%
See 3 more Smart Citations
“…However, the number of capture spiral turns (17.0 ± 4.3) was considerably greater than recorded for M. menardi in this study (6.0 ± 1.7), suggesting that the mesh height would be lower. A similar number of radii (16.9 ± 3.0) and spiral turns (13.0 ± 3.0) were observed in the facultative cave spider M. merianae , but this species does not show any reduction of frame threads and only a few mooring threads connect the web to the cave wall 41 . Interestingly, the webs of M. menardi were more symmetrical than the webs of the two surface-dwelling species.…”
Section: Discussionsupporting
confidence: 54%
“…The anapid Anapisona simoni shows more dramatic changes in frame, radial and capture threads that are somewhat similar to the responses observed in this study 69 , but anapid webs are very different from tetragnathid webs as they are more three-dimensional and lacking the non-sticky scaffolding spiral. Overall, comparisons between strongly constrained spiders in the laboratory and cave spiders in the wild have only limited validity as natural caves typically offers a range of potential web sites as demonstrated by the normal cave orb webs of the sympatric Metellina merianae 41 . Finally, it is also possible that the observed changes occur as a direct response to the low food availability in the subterranean habitats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies comparing different orb-weaver species living in the same local areas have predictably found that species with larger body sizes have larger capture areas within their webs (LeGuelte 1966;Carrel & Deyrup 2019;Hesselberg & Simonsen 2019). Many studies have found that larger individuals of a species tend to build larger webs, using either age categories (Kuntner et al 2008) or direct measurements of size of the spiders (Alam & Butt 2016).…”
mentioning
confidence: 99%